The multi-directional reach test in children with Down syndrome - Sawika Promsorn; Soontharee Taweetanalarp (World Scientific Publishing, 2021)
Objective: This study investigated the limits of stability (LOS) and the movement patterns during reaching by applying the Multi-Directional Reach Test (MDRT) in children with Down syndrome (DS) aged 7-12 years old. Methods: Thirty children with DS and 30 age and gender typical development (TD) matched children, aged 7-12 years old were recruited. Each child was asked to reach as far as possible during standing in four directions using a self-selected movement pattern. The movement patterns were classified by two experienced pediatric physical therapists. Results: The reach distance in children with DS aged 7-9 years old was significantly shorter than TD children aged 7-9 years old for the forward and backward directions. Also, the reach distance in DS children aged 7-9 years old was significantly smaller than that of TD children aged 10-12 years old for all directions. For children with DS aged 10-12 years old, the reach distance was significantly less than that of TD children only in the backward direction. All children with DS in this study adopt a hip and mixed strategy during forward and backward reaching. In contrast, TD children adopt an adult-like movement pattern. Conclusion: The boundary of stability in an anteroposterior (AP) direction of children with DS aged 7-12 years old was lesser than the matched TD children, especially for the backward direction. These findings may assist therapists in detecting postural control and balance problems in children with DS.